Bone and bone-substituting materials in plastic surgery of oroantral perforations of the maxillary sinus. (Texas Journal of Medical Science, 2026)
Oroantral perforations (OAP) and fistulas are common complications of maxillary tooth extraction and lateral alveolar surgery. Soft tissue closure of the defect does not always ensure restoration of bone volume, which is important for subsequent implant rehabilitation. The aim of this review was to analyze the use of bone and bone-substituting materials in OAP repair, taking into account morphological healing mechanisms and postoperative rehabilitation. An analysis of domestic and international publications on the use of autogenous bone grafts, allogeneic and xenogeneic osteoplastic materials, collagen membranes, and combined composites for the closure of maxillary sinus floor defects was conducted. It was shown that the use of bone or bonesubstituting materials helps maintain alveolar bone height, improve the quality of the regenerated bone, and promote the formation of a complete bone structure, which is morphologically associated with accelerated osteoconduction and angiogenesis. The choice of material determines the rehabilitation strategy and the timing of subsequent implantation